Notes on Extension of Fuzzy Complex Sets - Pishtiwan O. Sabir (Tikrit Journal of Pure Science)
The aim of this paper is to modify and improve the corresponding weakness results of multi-fuzzy complex numbers as an extension of fuzzy complex numbers, next we introduce and study the generalized multi-fuzzy complex numbers  and get some results. Lastly, we discuss the derivative of functions mapping complex numbers  into  as an extension of fuzzy complex derivatives.